Anthropometrics and Body Composition in Adults with High-Grade Gliomas: Effects of Disease-Related Variables. (3rd April 2018) - Bertoli, Simona; Battezzati, Alberto; Petruzzi, Alessandra; Leone, Alessandro; De Amicis, Ramona; Tramacere, Elena; Meda, Maddalena; Foppiani, Andrea; Silvani, Antonio; Lamperti, Elena
ABSTRACT: Nutritional status in adults with high-grade gliomas (HGGs) has been poorly investigated. We studied anthropometrics and fat mass (FM), fat free mass (FFM), and body water in HGGs patients also in relation to disease-related variables. Fifty-one patients (17 III and 34 IV-grade) and fifty-one control group (CG) matched for sex, age, and BMI were enrolled. Neurological scales, anthropometry, bioimpedance, and blood sampling were performed and analyzed according to grade, lesion location, extent of resection, phase of treatment, current steroids and antiepileptic therapy, and age of patient. 41.2% were overweight and 15.7% obese. Compared to the CG, HGGs had similar anthropometrics and body composition. IV-grade, compared to the III, had higher BMI, waist circumference, FM and lower FFM. Only patients during concomitant radio and chemotherapy showed a negative BMI variation from baseline. In conclusion, overnutrition occurs in almost 6 out of 10 HGGs patients and is more relevant in IV-grade. Throughout all the treatment phases, there is a higher risk of weight loss occurred only during concomitant radio and chemotherapy. Body composition showed no specific features compared to controls. These results may assist intervention studies directed towards neurometabolic dietary treatment. Nutritional screening is warranted during the time course of disease.